Detection of Serum Hs CRP and C3 Complement Levels Following Immunization with Measles Containing Vaccine in Iraqi Young Adults - Ismail Ibrahim Latif; Salwa S Abdul –Wahid; Arwa Mujahid Abdullah; Zena Jassim Mohammed (Diyala Journal of Medicine, 2019)
Background: Measles remains a  major cause of worldwide childhood mortality,  and    has  been  targeted  by  the  WHO  for  global  eradication following the eradication of poliomyelitis. Despite the implementation of mass school catch-up campaigns for measles, an outbreak of measles occurred mostly affecting the adult population.